Risk-appetite discriminated investors' portfolio optimization using regime-switching models: Comparative analysis between sharia-compliant and non-sharia-compliant stocks - Saleem, Hassan Mujtaba Nawaz (2021)
This study examines the portfolio wealth maximization (PWM) of risk-appetite discriminated (RAD) investors through technical analysis using regime-switching (RS) and non-RS models. The sample consists of 314 companies listed on Pakistan Stock Exchange (PSX), whereby 124 companies are Sharia-compliant (SC) and 190 companies are non-Sharia-compliant (NC), The daily data of stock prices from 18/11/2015 until 31 /05/2019 were collected from multiple secondary sources and processed through MATLAB software. The behavior of PSX is determined through exploratory data analysis (EDA) of various stylized facts' statistical descriptions and transition filtered probability forecasts (TFPF). Cumulated daily wealth (CDW) forecasts are checked and analyzed throughout the out-sample (OS) period. Moreover, cumulated ending wealth (CEW) and Sharpe ratio (SR) forecasts are also analyzed for robustness. Based on the strong asymmetric means and correlations observed during in-sample (IS)/OS and bull-market/bear-market periods movements, the PSX showed RS behavior. Further, the regime statistics and TFPF re-affirmed the findings where PSX switched 237 times between Regime-I and Regime-2 during 922 days trade. This study revealed that RS models-based portfolios' SC and NC stocks CEW increased 6.41 and 5.74 times, respectively. Unlike RS models, the non-RS models offer risk-appetite premium to the risk-taker investor but their CDWs, CEWs, and SRs are far low compared to their counterparts. Hence, RS models-based investment of RAD investors in SC stocks has outperformed. The current study contributes towards the portfolio optimization (PO) literature in context of random matrix theory (RMT) originated RS models applications to the emerging market Sharia screened stocks. The outcomes of this study are helpful for investors and traders in their portfolio diversification decision processes, and regulators and policymakers in their regulations formulation, policies articulation, and implementation decisions. Thus, the religiously compliant investments offer optimal PWM to the RAD investors who invest through RS models-based strategies in RS markets.